The Later Years: Women Instructors at the Winnipeg School of Art in the 1940s - Baker, Marilyn (Atlantis, 2006)
Women were employed as art teachers at the Winnipeg School of Art in Winnipeg, Manitoba, in unusual numbers from 1940 to 1950. Beneficiaries of a proper art education, they "kept the home fires burning." When the men came back they were let go in what was seen as a return to normalcy.